Implementation of Pancasila Student Profiles at Madrasah Aliyah Negeri 2 Kediri City - adjeng afidah Nurrohamah; Seli Septiana Pratiwi (Buana Pendidikan, 2023)
This research wants to show and describe the application of the project to strengthen the profile of Pancasila students in MAN 2 Kediri City, where MAN 2 Kediri City became the pioneer in implementing the independent curriculum which was under the auspices of the Ministry of Religion. The research method used is descriptive qualitative with data collection through observation, interviews, and documentation. The subjects in this study were curriculum representatives, facilitating teams, and students of MAN 2 Kota Kediri. The results showed a lack of understanding regarding the project to strengthen the profile of Pancasila students from both the facilitating team and the students. MAN 2 Kota Kediri to encourage the successful implementation of the project to strengthen the profile of Pancasila students by creating a Pancasila student profile expo program, the aim of which is to showcase and demonstrate the results of the project to strengthen students' Pancasila student profiles. The theme applied by MAN 2 Kediri City is local wisdom and wake up the soul, wake up the body, its implementation results in students experiencing the inculcation of the character of the two themes through a series of project processes to strengthen the profile of Pancasila students.